Usability Evaluation of Islamic Learning Mobile Applications - Syeda Hamna Bibi; Rumsha Muhammad Munaf; Narmeen Zakaria Bawany; Arifa Shamim; Zara Saleem (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : The trend of using mobile devices for the purpose of learning is gaining momentum. Apart from traditional education, various applications are being developed for religious learning. Pakistan is inhabited by around 98% of Muslims.  Hence, the informal learning of Islam is essential for Muslim child development. This research presents a usability study of different Islamic learning mobile applications available on the android platform for children. The purpose of this research is to evaluate the usability of different Islamic learning mobile applications for children of diverse age groups in order to understand what design principles must be followed that increase the usability of the application. The main focus of this research is to observe and evaluate how easily children of different age groups respond to different applications, how effectively the children understand the core features of the applications and how easily they are able to use the application by themselves.